AN ANALYSIS OF GRAMMATICAL ERRORS MADE BY 3rd-YEAR THAI BUSINESS ENGLISH UNDERGRADUATES WHEN SPONTANEOUSLY WRITING NARRATIVE AND DESCRIPTIVE PARAGRAPHS - Goldsmith, Anthony; Sujaritjan, Pattanan (International Journal of Research -GRANTHAALAYAH, 2020)
This research reviews the grammatical errors written by sixty-eight, 3rd-year, Thai, Business English undergraduates when spontaneously writing narrative and descriptive paragraphs. The data was analysed using percentages, mean scores, standard deviation scores, and t-test p-values. The research results show that the students wrote 837 sentences with a mean score of 6.154 sentences per paragraph. 86 were written correctly and 751 were written incorrectly with 2131 grammar errors. The grammatically correct written sentences were all simple sentences. The most frequent errors identified were 227 verb (V) errors (10.652% of identified errors). There is a mean of 31.338 errors per participant (SD 9.957), a mean of 15.669 errors per paragraph, and a mean of 2.837 errors for each incorrectly written sentence. The female participants wrote a mean score of 12.685 sentences, which is 16.84% more than the males who wrote a mean of 10.857 sentences. Three error types by gender showed a high level of significance. These were noun errors with a t-test p-value of 0.012, punctuation errors with a t-test p-value of 0.037, and conjunction errors with a t-test p-value of 0.081. The female students made a significantly higher number of errors in these three error groups.